2020
DOI: 10.12928/dpphj.v14i2.1912
|View full text |Cite
|
Sign up to set email alerts
|

The Trends of Neonatal Mortality Rate Among South East Asia Countries from 2000-2017

Abstract: Background: Neonatal MortalityRate (NMR) reflects the quality of health services provided by the government. It is very important to disclose the health system capability of each country in managing mother and child health programs because it is an essential health policy that should be prioritized.  The health system capability of a country will determine the welfare and social guarantee because most of NMR causes are preventable. Several components such as maternal factors, neonatal and health services were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Another study in South-East Asia stated that the main cause of death in the region is prematurity, perinatal asphyxia, and congenital anomaly. Indonesia also has the highest NMR compared to other South-East Asian Countries (Soleman, 2020b).…”
Section: Cause Of Deathmentioning
confidence: 97%
“…Another study in South-East Asia stated that the main cause of death in the region is prematurity, perinatal asphyxia, and congenital anomaly. Indonesia also has the highest NMR compared to other South-East Asian Countries (Soleman, 2020b).…”
Section: Cause Of Deathmentioning
confidence: 97%
“…The systematic review conducted in Brazil showed that the average neonatal mortality rate was 9.46 deaths/1,000 live births in 2017, with a reduction of 2.15% between 2007 to 2017[17]. In the systematic review from South East Asia Countries Indonesia was the country with the highest neonatal mortality of 61 live births per 1000 live birth in 2017, the trend decreased gradually from 103 per 1000 live birth in 2000[18]. In Nepal though the neonatal mortality is decreasing, if it continues with current rate, it will take another 50 years for the country to attain the 2030 SDG target.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the density of healthcare workers in Vietnam, including physicians, midwives, and nurses, increased life expectancy and decreased pediatric mortality (Nyugen et al., 2016). More than half of the 10 ASEAN member states are developing countries that may face challenges in reducing mortality of children under five years (Soleman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advancements, the Health Sector Strategic Plan of the Ministry of Health still faces numerous obstacles in providing healthcare in Cambodia. The previous strategic plan ( Ministry of Health, 2016-2020HSP3) identified gaps between the established quality of healthcare standards of practice, clinical practice guidelines, and available health service quality. The Health Sector Human Development Plan 2016-2020, with its five strategic goals, was launched by the Ministry of Health that culminate in building a unified approach to ensure a qualified health professional workforce that will continue to meet the needs of its growing population, addressing workplace environment needs, improving the quality of education, and strengthening the regulatory capacity within healthcare (University of Health Sciences, 2019).…”
Section: Introductionmentioning
confidence: 99%